Collaboration in anthropology: the (field)work of grounded practice - Hilton, Amanda (Cambio. Rivista sulle Trasformazioni Sociali, 2018)
This essay uses ongoing ethnographic research with olive and olive oil producers in Sicily, Italy, as a springboard to reflect on collaboration in anthropology. I provide a brief review of various approaches to collaboration in anthropology and discuss the potential of practice theory and correspondence (Gatt and Ingold 2013, Ingold 2017b) to collaborative anthropology. I offer this reflection through the lens of my ongoing fieldwork as one example of how power dynamics and positionality in and out of the field shape what types of collaborations are possible and may be potentially fruitful.